Impact of Renal Function on Long-Term Clinical Outcomes in Patients With Coronary Chronic Total Occlusions: Results From an Observational Single-Center Cohort Study During the Last 12 Years - Guo, Lei; Ding, Huaiyu; Lv, Haichen; Zhang, Xiaoyan; Zhong, Lei; Wu, Jian; Xu, Jiaying; Zhou, Xuchen; Huang, Rongchong (Frontiers in Cardiovascular Medicine, 2020)
Background: The number of coronary chronic total occlusion (CTO) patients with renal insufficiency is huge, and limited data are available on the impact of renal insufficiency on long-term clinical outcomes in CTO patients. We aimed to investigate clinical outcomes of CTO percutaneous coronary intervention (PCI) vs. medical therapy (MT) in CTO patients according to baseline renal function. Methods: In the study population of 2,497, 1,220 patients underwent CTO PCI and 1,277 patients received MT. Patients were divided into four groups based on renal function: group 1 [estimated glomerular filtration rate (eGFR) ≥ 90 ml/min/1.73 m2], group 2 (60 ≤ eGFR <90 ml/min/1.73 m2), group 3 (30 ≤ eGFR <60 ml/min/1.73 m2), and group 4 (eGFR <30 ml/min/1.73 m2). Major adverse cardiac event (MACE) was the primary end point. Results: Median follow-up was 2.6 years. With the decline in renal function, MACE (p < 0.001) and cardiac death (p < 0.001) were increased. In group 1 and group 2, MACE occurred less frequently in patients with CTO PCI, as compared to patients in the MT group (15.6% vs. 22.8%, p < 0.001; 15.6% vs. 26.5%, p < 0.001; respectively). However, there was no significant difference in terms of MACE between CTO PCI and MT in group 3 (21.1% vs. 28.7%, p = 0.211) and group 4 (28.6% vs. 50.0%, p = 0.289). MACE was significantly reduced for patients who received successful CTO PCI compared to patients with MT (16.7% vs. 22.8%, p = 0.006; 16.3% vs. 26.5%, p = 0.003, respectively) in group 1 and group 2. eGFR < 30 ml/min/1.73 m2, age, male gender, diabetes mellitus, heart failure, multivessel disease, and MT were identified as independent predictors for MACE in patients with CTOs. Conclusions: Renal impairment is associated with MACE in patients with CTOs. For treatment of CTO, compared with MT alone, CTO PCI may reduce the risk of MACE in patients without chronic kidney disease (CKD). However, reduced MACE from CTO PCI among patients with CKD was not observed. Similar beneficial effects were observed in patients without CKD who underwent successful CTO procedures.